Frequency and Severity of Adverse Drug Reactions to Medications Prescribed for Alzheimer’s Disease in a Brazilian City: Cross-Sectional Study - Ferreira, Tânia Regina; Lopes, Luciane Cruz; Bergamaschi, Cristiane de Càssia (Frontiers in Pharmacology, 2020)
Background: There is lack of national studies that assess the risks associated with the drugs provided under the Brazilian public health system for treating Alzheimer’s disease. Then, this study determined the prevalence and severity of self-reported adverse drug reactions (ADRs) to medications prescribed to patients with Alzheimer’s disease in the Brazilian public health system. Methods: A cross-sectional study was carried out based on public data from the MEDEX system (information on dispensing data, known as exceptional dispensing medications) and interviews with patients and/or caregivers who get access to Alzheimer’s drugs at a public pharmacy in a large Brazilian city, between July and September 2017, inquiring about medication-related adverse drug reactions (ADRs) and serious adverse events (SAEs). Results: The subjects were asked about ADRs and serious adverse events (SAEs) related to the use of donepezil, galantamine, rivastigmine and memantine. Out of 285 patients enrolled on the database, 250 participated in the study (87.7%). Among the participants, approximately 63.0% were female, 70.3% aged ≥75 years and 70.3% had comorbidities. Overall, 209 patients (83.6%) reported at least one ADR (total 1,149 ADRs) and rivastigmine was associated with the largest number of ADRs per patient (7.9 ADRs/patient). The predominant adverse effects were psychiatric disorders with common frequency (57.1%) and mild severity (89.0%). Six patients (2.4%) had SAEs that required hospitalization. The use of antipsychotics was the variable associated with ADR (OR= 4.95; 95%CI: 1.45–16.93; p=0.011). Conclusions: There was a large number of reported ADRs and most of them were of common frequency and mild severity, being mainly related to psychiatric disorders. Considering the fragility of these patients, it is important to improve safety-related care in the use of drugs for treating this disease. Keywords: older adults, Alzheimer’s disease, adverse reaction to drugs, safety, pharmacoepidemiology, safety.